Severity and workload of nursing with patients seeking admission to an intensive care unit - Castro, Meire Cristina Novelli E; Dell'acqua, Magda Cristina Queiroz; Unger, Igor Chagas; Cyrino, Claudia Maria Silva; Almeida, Priscila Masquetto Vieira De (Universidade Federal do Rio de Janeiro, 2018)
AbstractObjective: To identify the severity and workload of nursing with adult patients seeking admission to an Intensive Care Unit (ICU).Methods: A cross-sectional study with a quantitative, exploratory and prospective approach was performed, developed in a hospital in the state of São Paulo. Demographic data on patients were collected, the Simplified Acute Physiology Score III (SAPS III) was applied to assess the severity of patients and the Nursing Activities Score (NAS) was used to evaluate nursing workload, between July and August 2014.Results: The overall mean score of the SAPS III was 30.52 ± 18.39 and that of the NAS was 58.18 ± 22.29. The group of patients admitted to the ICU showed higher severity and higher workload of nursing compared to non-admitted patients. Non-admitted patients had an NAS of 53.85.Conclusion: The nursing workload in patients who were not admitted to the ICU was also high. The evaluation of workload in other contexts where patients are seriously ill is important. The workload assessment in other contexts where severely ill patients are found is evident.

ResumenObjetivo: Identificar la gravedad y la carga de trabajo de enfermería requerida por pacientes adultos candidatos a una vacante en Unidad de Terapia Intensiva (UTI).Método: Estudio transversal, cuantitativo, exploratorio y prospectivo, realizado en un hospital del interior de São Paulo. La recolección de datos demográficos utilizó el Simplified Acute Physiology Score III (SAPS III), para evaluar la gravedad, y el Nursing Activities Score (NAS), para evaluar la carga de trabajo de enfermería, entre julio y agosto de 2014.Resultados: El promedio general de la puntuación SAPS III fue 30,52; el NAS, 58,18. Los pacientes admitidos en la UTI presentaron mayor gravedad y carga de trabajo en comparación con pacientes no admitidos (NAS promedio de 53,85).Conclusión: La carga de trabajo de enfermería en los pacientes que no son admitidos en la UTI también es alta. Se debe evaluar la carga de trabajo en otros contextos donde estén pacientes graves.

ResumoObjetivo: Identificar a gravidade e a carga de trabalho de enfermagem requerida por pacientes adultos candidatos à vaga em Unidade de Terapia Intensiva (UTI).Método: Estudo transversal, quantitativo, exploratório e prospectivo, realizado em um hospital do interior do estado de São Paulo. Foram coletados os dados demográficos dos pacientes, o Simplified Acute Physiology Score III (SAPS III) para avaliar a gravidade e o Nursing Activities Score (NAS) para avaliar a carga de trabalho, entre julho e agosto de 2014.Resultados: A média geral do escore SAPS III foi 30,52 ± 18,39 e do NAS foi 58,18 ± 22,29. Os pacientes admitidos na UTI apresentaram maior gravidade e carga de trabalho em comparação com os não admitidos. Os pacientes não admitidos apresentaram NAS médio de 53,85.Conclusão: A carga de trabalho de enfermagem nos pacientes que não são admitidos na UTI também é alta. Evidencia-se a avaliação da carga de trabalho em outros contextos onde estejam pacientes graves.
Gravedad y carga de trabajo de enfermería de pacientes candidatos a la vacante de unidad de cuidados intensivos
Gravidade e carga de trabalho de enfermagem em pacientes candidatos à vaga na UTI
Keywords: Severity of Illness Index; Workload; Nursing; Intensive Care Units; Personnel Management; Índice de Gravidade de Doença; Carga de trabalho; Enfermagem; Unidade de Terapia Intensiva; Administração de recursos humanos